PENGRAJIN NOKEN PADA SUKU BANGSA AMUNGME DI DESA LIMAU ASRI KECAMATAN IWAKA KABUPATEN MIMIKA PROVINSI PAPUA - Dekme, Dedi (Universitas Sam Ratulangi, 2015)
Noken craftsmen Amungme Tribe is one of the odd jobs done by a woman, and has been entrenched in their minds. Activity Amungme women are weaving Noken. Noken weaving tradition is knowledge Amungme women followed for generations. Since the Amungme women born until she was grown up, they are nurtured by his mother constantly until the age of 6-7 years can weave Nokens her own.Noken is bags Papuans. Made of twisted roots shaped nets, Noken is a multi-functional tool that fit to carry vegetables and fruits, as well as holding the baby even pigs. In the life of Amungme village craftsmen Nokens Lemons Asri, many natural potential to enrich the lives of Craftsmen Noken, one of the only activities carried Craftsmen Nokens namely, collecting materials Nokens makers of natural products, the activity of preparing the tools or materials maker noken is an activity that entrenched in the minds of Craftsmen noken.Noken weave can not determine the time when, and the place where, because almost all the time and wherever they are, Amungme women weave Noken, plain weave Amungme Women Noken in the market, where sorrow, in kendarahan. Noken synonymous with women, and Noken symbolizes the presence of women.Keywords: Noken, craftsmen, Amungme